Enhancing Vocabulary Acquisition with Fairy Tale Audio in English Lesson at SMAN 1 Mayong Jepara - Salsabila Kurnia Putri; Ririn Ambarini; Ajeng Setyorini (INDO PUBLISHING, 2025)
This study investigates the effectiveness of using audio fairytales as a medium to enhance vocabulary acquisition among eleventh-grade students at SMAN 1 Mayong, specifically students from class XI-10. The research employed a one-group pretest-posttest design to assess students’ vocabulary mastery before and after the intervention. The treatment consisted of two learning sessions using audio fairytales, delivered through structured and interactive listening activities. Data were collected via pre-tests and post-tests measuring both receptive and productive vocabulary knowledge. The results demonstrated a significant improvement in students’ vocabulary acquisition, with the mean score increasing markedly from 42.78 in the pre-test to 91.11 in the post-test. Statistical analysis using the paired sample t-test confirmed the difference was statistically significant (p-value = 0.000). The effect size was large, with Cohen’s d at 19.29 and Hedges’ correction at 19.71, indicating a strong impact of the intervention. These findings suggest that integrating audio fairytales into English instruction is an effective approach to fostering vocabulary development, enhancing student engagement, and supporting meaningful language retention